2023
DOI: 10.1136/bmjopen-2022-067549
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards participating in research involving digital pill systems to measure oral HIV pre-exposure chemoprophylaxis: a cross-sectional study among men who have sex with men with substance use in the USA

Abstract: ObjectivesThis quantitative survey sought to understand, among men who have sex with men (MSM) with potentially problematic substance use, the attitudes towards participation in research involving digital pill systems (DPS) for HIV pre-exposure prophylaxis (PrEP) adherence measurement, and the barriers and facilitators to research participation.DesignOne-time, cross-sectional, online sampling-based survey.SettingUS social networking app predominantly focused on MSM.ParticipantsMSM without HIV who reported curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Our findings are in line with those of Chai et al [56], who reported from qualitative interviews that 15 out of 90 persons using a digital pill system (DPS) [2] for PrEP adherence measurement perceived the device as acceptable, novel, and valuable. Interestingly, men who have sex with men (MSM) taking PrEP who reported substance use were also found to have positive perceptions toward using the DPS in the future [57]. Notably, the PrEP cohort we studied had significantly higher levels of UX satisfaction with the DHFS than that reported in participants in a psychiatric study population (greater than 75% vs 53%, respectively) [58].…”
Section: Principal Findingsmentioning
confidence: 72%
See 1 more Smart Citation
“…Our findings are in line with those of Chai et al [56], who reported from qualitative interviews that 15 out of 90 persons using a digital pill system (DPS) [2] for PrEP adherence measurement perceived the device as acceptable, novel, and valuable. Interestingly, men who have sex with men (MSM) taking PrEP who reported substance use were also found to have positive perceptions toward using the DPS in the future [57]. Notably, the PrEP cohort we studied had significantly higher levels of UX satisfaction with the DHFS than that reported in participants in a psychiatric study population (greater than 75% vs 53%, respectively) [58].…”
Section: Principal Findingsmentioning
confidence: 72%
“…Significant differences were observed between questionnaire nonrespondents and respondents, limiting the generalizability of our findings to persons taking PrEP who are homeless or use methamphetamine. In the latter regard, it is notable that Chai et al [56,57] report positive UX and attitude findings regarding DPS technology in MSM taking PrEP who use substances. Despite being one of the largest detailed study available on UX in persons who used an IS medication adherence system, our sample size was limited, and as the probability of reporting a positive experience was observed in >75% of the study population, the likelihood of identifying "current and future use personas" across our study was restricted by our sample size.…”
Section: Limitationsmentioning
confidence: 99%
“…Details on the parent sample (N = 157) are reported elsewhere [ 11 ]. In this subsample analysis, only individuals who reported at least a slight willingness (1 = not at all, 2 = slightly, 3 = moderately, 4 = very, 5 = extremely willing) to participate in DPS-related research and self-identified as cisgender males were included (N = 131).…”
Section: Resultsmentioning
confidence: 99%
“…Previous qualitative work demonstrated that MSM with substance use are accepting of DPS technology, willing to operate it in the real world to measure PrEP adherence, and perceive value in having on-demand access to PrEP adherence data [ 8 , 10 ]. Additionally, a recent study surveyed a national sample of MSM on PrEP who use substances to understand broader perceptions of the DPS and willingness to interact with the system for PrEP adherence measurement [ 11 ]. The results were congruent with previous qualitative work demonstrating the willingness of MSM on PrEP who use substances to interact with the DPS.…”
Section: Introductionmentioning
confidence: 99%